2008
DOI: 10.1038/jp.2008.141
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reference ranges for neonates, defined using data from over 47 000 patients in a multihospital healthcare system

Abstract: Objective: Identifying a platelet count as abnormal (thrombocytopenia or thrombocytosis) can facilitate recognizing various disease states. However, the published reference ranges for platelet counts in neonates may be imprecise, as they were generated from relatively small sample sizes and compiled before modern platelet enumeration methods. Study design:We derived new neonatal reference ranges for platelet counts and mean platelet volume (MPV) measurements using electronic data accumulated during a recent 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(147 citation statements)
references
References 44 publications
6
136
1
4
Order By: Relevance
“…25 Recently, PLT count and MPV reference ranges for the first 3 days of life were reported for neonates in a large, multi-hospital study. 26 The association of MPV and PLT count with Hb and RBC concentration of CB collections from healthy term infants is interesting. Animal studies have shown that the hematopoietic activity is strictly regulated genetically.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recently, PLT count and MPV reference ranges for the first 3 days of life were reported for neonates in a large, multi-hospital study. 26 The association of MPV and PLT count with Hb and RBC concentration of CB collections from healthy term infants is interesting. Animal studies have shown that the hematopoietic activity is strictly regulated genetically.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Because several studies have shown that reference values of platelet count in fetuses reach adult values early in gestation, it is unlikely that this correlation is confounded by gestational age. [22] Associations between platelet count and birth weight have been demonstrated before, but these birth weight groups included both AGA and SGA neonates. [4] Our results suggest that the severity of SGA, and not birth weight alone, is correlated with neonatal platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the endothelium and platelets is, to a large extent, dependent on the total number of platelets, their function and the activity of VWF. By 22 weeks gestation, the well fetus has a platelet count within the adult normal range at 247 AE 59 9 10 9 /l, which remains at similar levels until term (Forestier et al, 1991) but then rises during the first 9 week of life up to 750 9 10 9 /l (Wiedmeier et al, 2009). …”
Section: Plateletsmentioning
confidence: 99%